COMPARATIVE ANALYSIS OF MACEDONIAN AND ALBANIAN ACCOUNTING AND INTERNATIONAL FINANCIAL REPORTING STANDARDS FRAMEWORK - Deari, Fitim Satki (Revista Universo Contábil, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> The purpose of the paper is to compare national accounting standards of Macedonia and Albania with International Accounting Standards of the International Financial Reporting Standards (IAS/IFRS). It looks at approaches of these two countries regarding the aspects of financial reporting and analyses differences and similarities. The paper also analyzes the characteristics of both accounting systems, and it examines the main changes that have been made in recent years. It presents the main differences and similarities in accounting practices with the particular emphasis on tangible and intangible assets, inventories and money. The adoption of IFRS is supported in many countries inside and outside the European Union, including Macedonia and Albania. There have been made many changes in IFRS implementation in both accountings systems. As a result of economic integration, the harmonization of financial reporting has become important for both countries. Â 